Experiences of organizing the social institutions into non-profit companies in Hajdú-Bihar county - Verdó, György (Acta Agraria Debreceniensis, 2012)
The study attempts to find solutions for relieving the major serious economic and social problems which are resulted partly by the economic crisis, mainly by demographic processes ( decrease of population, declining economic activity, ageing) and which occur all over Europe. In 2007, in Hungary, the Local Government of Hajdú-Bihar county started to reform the social institutions sytems in a unique way in the interest of operating these systems economically. The experiences, gained after the conversion, show that the companies as social institutions maintainers are able to work properly more efficiently, with less government support while they meet the professional requirements, and the management who does the control is competentand innovative.